Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1468-0297.2009.02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Focal Points: Cognitive Hierarchy Theory versus Team Reasoning

Abstract: This article reports experimental tests of two alternative explanations of how players use focal points to select equilibria in one-shot coordination games. Cognitive hierarchy theory explains coordination as the result of common beliefs about playersÕ pre-reflective inclinations towards the relevant strategies; the theory of team reasoning explains it as the result of the playersÕ using a non-standard form of reasoning. We report two experiments. One finds strong support for team reasoning; the other supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
163
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(182 citation statements)
references
References 20 publications
14
163
0
1
Order By: Relevance
“…The reason why the respondents chose this location was that it had a strong salience or prominence that led to a meeting of minds or mutual understanding of where to meet in the city. Schelling's findings from his experiments have been confirmed by many other researchers, 19 including Mehta, Starmer and Sugden (1994a;1994b), Bacharach and Bernasconi (1997), Crawford et al (2008), Bardsley et al (2010) and Isoni et al (2013).…”
Section: Tacit Collusionsupporting
confidence: 69%
“…The reason why the respondents chose this location was that it had a strong salience or prominence that led to a meeting of minds or mutual understanding of where to meet in the city. Schelling's findings from his experiments have been confirmed by many other researchers, 19 including Mehta, Starmer and Sugden (1994a;1994b), Bacharach and Bernasconi (1997), Crawford et al (2008), Bardsley et al (2010) and Isoni et al (2013).…”
Section: Tacit Collusionsupporting
confidence: 69%
“…In spite of this vicious circle, the Hi-Lo game induces a powerful intuition in human decision makers that H is the rational choice, and experimental evidence confirms that virtually all players choose it (Bardsley, Mehta, Starmer, & Sugden, 2010). What accounts for this phenomenon?…”
Section: Payoff Dominancementioning
confidence: 99%
“…She showed that a player has no reason at all to choose a strategy associated with a salient focal point in the absence of an independent reason to expect the co-player to choose it. Furthermore, any attempt to derive, from the standard assumptions, a reason to expect a coplayer to choose it generates a version of the vicious circle discussed above without leading to any conclusion, and this is now generally acknowledged by game theorists (e.g., Anderlini, 1999;Aumann & Sorin, 1989;Bacharach, 2006, Chapter 1;Bardsley et al, 2010;Janssen, 2001Janssen, , 2006.…”
Section: Two Common Fallaciesmentioning
confidence: 99%
“…Bardsley et al (2010), for instance, provide evidence of a correlation between choices in coordination games and a postexperiment questionnaire on favourites.…”
Section: The Rulesmentioning
confidence: 99%
“…Bacharach and Bernasconi (1997) and Bardsley et al (2010) find some support for such choices: e.g. Mannheim was chosen in the set {Mannheim, Berlin, Brussels, Lisbon, Madrid} and glass in the set {glass, diamond, emerald, sapphire}.…”
Section: The Rulesmentioning
confidence: 99%